The Production of Compressed Charcoal Fuel from the Waste Materials Collected after Processing Khao-Larm - วิรุณพันธ์ กานต์; สายเปลี่ยน ธนารักษ์; ใจชมพู ภาคภูมิ (RMUTL Engineering Journal, 2017)
This research involves the production of compressed charcoal from the waste materials gathered in Khao-Larm processing. The implemented waste materials, including coconut shell and bamboo, were carbonized and ground before being mixed to the appropriate ratio. In the mixing process, the charcoal powder was combined with 0.5 kilograms of flour and 3 liters of water as a binder in order to produce compressed charcoal fuel. In this experiment there were 11 different formulas of the mixture to be tested. Each mixture was molded and formed into a hexagonal shape by a screw compress machine, and then dehumidified by 8% following the Community Product Standard (TCPS. 238/2547). The thermal efficiency of the compressed charcoal fuel was examined in order to identify the moisture content, thermal energy, compressive stress and fuel consumption quantity by boiling 3 liters of water at 80 degrees Celsius. The result found that the most appropriate ratio was on formula 3, (8.55 kilograms of coconut shell and 0.95 kilograms of bamboo powder). Formula 3 showed the highest efficiency amongst the 10 formulas, with a moisture content of 6.07 percent, an ash content of 10.42 percent, 5748.83 kilocalories per kilogram of thermal energy, 892.530 newton per square millimeters of compressive stress, and 1.917 kilogram per hours of fuel consumption. The key implications of this research are focused on the waste reduction from Khao-Larm processing and the benefits of recycling the bamboo waste into fuel and renewable energy.